Analysis of Financial Performance from Synergistic Value Pre and Post Merger and Acquisition - Tarigan, Louis Yosen Primsa; Lie, Michelle (Jurnal Ekonomi, 2022)
The purpose of this study is to examine the synergistic effect on the financial performance of PT Bank Mandiri Tbk three years before and after acquisition period of PT Asuransi Jiwa InHealth using the Risk-Based Bank Rating Model. Financial ratios being used in this study are based on the three measurements Risk-Based Bank Rating bank soundness level criteria including, risk profile, earnings, and capital. The study is then continued with further analysis of reasoning regarding the impact of synergistic effect towards mergers and acquisitions’ financial performance. The result of this study indicates that there is no improvement in risk profile after acquisition because of increasing trend of credit risk with non performing loan as the indicator. Whereas earnings and capital have shown improvement after acquisition despite decreasing trend of net interest margin due to slowing down economy of Indonesia. Overall, it can be said that PT Bank Mandiri Tbk has always maintaining excellent financial performance before and after acquisition period of PT Asuransi Jiwa InHealth.